Challenging Residual Contamination of Instruments for Robotic Surgery in Japan. (31st October 2016) - Saito, Yuhei; Yasuhara, Hiroshi; Murakoshi, Satoshi; Komatsu, Takami; Fukatsu, Kazuhiko; Uetera, Yushi
Abstract : BACKGROUND: Recently, robotic surgery has been introduced in many hospitals. The structure of robotic instruments is so complex that updating their cleaning methods is a challenge for healthcare professionals. However, there is limited information on the effectiveness of cleaning for instruments for robotic surgery. OBJECTIVE: To determine the level of residual contamination of instruments for robotic surgery and to develop a method to evaluate the cleaning efficacy for complex surgical devices. METHODS: Surgical instruments were collected immediately after operations and/or after in-house cleaning, and the level of residual protein was measured. Three serial measurements were performed on instruments after cleaning to determine the changes in the level of contamination and the total amount of residual protein. The study took place from September 1, 2013, through June 30, 2015, in Japan. RESULTS: The amount of protein released from robotic instruments declined exponentially. The amount after in-house cleaning was 650, 550, and 530 µg/instrument in the 3 serial measurements. The overall level of residual protein in each measurement was much higher for robotic instruments than for ordinary instruments ( P <.0001). CONCLUSIONS: Our data demonstrated that complete removal of residual protein from surgical instruments is virtually impossible. The pattern of decline differed depending on the instrument type, which reflected the complex structure of the instruments. It might be necessary to establish a new standard for cleaning using a novel classification according to the structural complexity of instruments, especially for those for robotic surgery. Infect Control Hosp Epidemiol 2017;38:143–146